Listening to the music the machines make : inventing electronic pop 1978-1983 - Evans, Richard, 1967 September 19- (Omnibus Press, 2022)
Listening to the Music the Machines Make is the revolutionary story of electronic pop from 1978 to 1983, a true golden age of British music. This definitive account explores how krautrock, disco, glam rock and punk inspired a new generation to rip up the rulebook and venture toward a new frontier of electronic music - one that laid the foundations for Hip-Hop, house, techno and beyond. Including an extensive collection of archive images throughout, Richard Evans's kaleidoscopic narrative draws on years of research, a plethora of archive press materials and the input of key figures, including Vince Clarke (Depeche Mode, Yazoo, Erasure), Martyn Ware (The Human League, B.E.F., Heaven 17) and Daniel Miller (The Normal, Mute Records). From the gritty and experimental to the camp and theatrical, this book charts the careers and impact of electronic pop's earliest innovators and luminaries, from Devo, The Normal, Telex and Cabaret Voltaire to Soft Cell, Gary Numan, OMD, Duran Duran, Depeche Mode.
Keywords: Electronica (Music) -- History and criticism.; Electronic dance music -- History and criticism.; Popular music -- 1971-1980 -- History and criticism.; Popular music -- 1981-1990 -- History and criticism.; Électronica (Musique) -- Histoire et critique.; Dance music -- Histoire et critique.; Musique populaire -- 1971-1980 -- Histoire et critique.; Musique populaire -- 1981-1990 -- Histoire et critique.; History & Criticism.; MUSIC.; Pop Vocal.; Genres & Styles.; Electronic dance music; Electronica (Music); Popular music; 1971-1990; Criticism, interpretation, etc.; Popular music.; Musique populaire.